STUDY ON FATIGUE SCATTER FACTOR OF AIRCRAFT STRUCTURE UNDER DURABILITY SEVERE LOAD SPECTRUM - WANG YongJun; LI Tang; DUI HongNa (Jixie qiangdu)
Fatigue scatter factor is the reliability index of aircraft structure life,which is used to describe the reliability of analysis and test results. When average spectrum is used for durability analysis,the scatter factor is generally set as 4,corresponding to 99. 9% reliability. In the case of using severe spectrum,the scatter factor is between 2 and 4,but the specific value is not clear in aircraft strength specification. By referring to a larger number of relevant research and according to the results of scatter study on component-level fatigue tests,the fatigue scatter factor of aircraft structures under severe spectrum was clarified,which lays a foundation for the application of durability severe spectrum in fatigue design and full-scale test of military aircraft.